Experimental Study of Process Parameter Effects on Internal Defects in Titanium Coaxial Wire-Based Laser Metal Deposition - Remy Mathenia; Braden McLain; Todd Sparks; Frank Liou (Metals)
Wire-based laser metal deposition is an additive manufacturing process that can be used in the efficient manufacturing of complex structures. This paper utilizes a three-beam coaxial laser wire system to explore the effect of process parameters on the resultant deposition density. The reduction in or elimination of defects is important to the mechanical properties of the additively manufactured material and the widespread adoption of additive manufacturing processes. In this work, two-bead-wide walls were deposited under varying experimental conditions, including the traverse feed rate and workpiece illumination proportion. A method for calculating the bead pitch and layer height increment based on the geometry of the deposited material was developed. The deposited samples were micro-CT-scanned to characterize internal defects at a high resolution. The volume of the detected defects was measured and compared to the total sample volume to calculate a defect rate for each run of the experiment. The traverse feed rate and defocusing level were found to have a significant impact on the output defect rate. As these process parameters were increased, the defect rate decreased. Across the experimental levels, the defect volume percentage was reduced from 1.021% to 0.062%. This reduction in internal defect size enhances the material’s mechanical performance and ensures its suitability for aerospace applications.